Development of thermal memory cells on silicon using the floating zero algorithm - Yury N. Kulchin; Arkady A. Skvortsov; Vladimir K. Nikolaev; Olga V. Volodina (Scientific Reports)
Abstract In this article, we investigate the development and use of thermal memory elements based on thin-film aluminum devices on silicon wafer. To stabilize their operation and reduce the number of errors during the read/write process of thermal information in such devices, we propose an algorithm (referred to as the floating zero algorithm) for adjusting the temperature conditions of thermal memory cells. This algorithm controls the thermal memory cells on silicon under varying ambient temperature conditions. We tested the algorithm performance using an experimental thermal memory sample at room temperature. Additionally, we conducted a study on the degradation process of the sample under high electrothermal loading conditions. The results showed that the degradation process in the sample starts when a single current pulse of duration τ i  ≥ 100 µs and amplitude density j i ≥ 8.5 × 1010 A/m2) flows through the device. We propose a criterion for determining the safe operation area γ of the device under investigation and experimentally determine its value γ = 6.0(VA√s).